2003
DOI: 10.1002/chem.200390092
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in Metal Oxides

Abstract: A fascinating phenomenon, recently found to occur in certain transition-metal oxides, is phase separation wherein pure, nominally monophasic oxides of transition metals with well-defined compositions separate into two or more phases over a specific temperature range. Such phase separation is entirely reversible, and is generally the result of a competition between charge-localization and -delocalization, the two situations being associated with contrasting electronic and magnetic properties. Coexistence of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Nowhere is it manifested better than the rare-earth manganites. Thus, these materials of high chemical homogeneity consist of different spatial regions with different electronic order (Mathur & Littlewood 2003;Rao et al 2004;Dagotto 2005;Shenoy et al 2006), a phenomenon that has come to be known as 'phase separation'. These regions can be static or dynamic and can be tuned by the application of external stimuli like a magnetic field.…”
Section: Electronic Inhomogeneities In Rare-earth Manganitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowhere is it manifested better than the rare-earth manganites. Thus, these materials of high chemical homogeneity consist of different spatial regions with different electronic order (Mathur & Littlewood 2003;Rao et al 2004;Dagotto 2005;Shenoy et al 2006), a phenomenon that has come to be known as 'phase separation'. These regions can be static or dynamic and can be tuned by the application of external stimuli like a magnetic field.…”
Section: Electronic Inhomogeneities In Rare-earth Manganitesmentioning
confidence: 99%
“…In addition, there is overwhelming evidence that these oxides with high chemical homogeneity can show spatially inhomogeneous structures, i.e. regions showing different electronic orders (Mathur & Littlewood 2003;Rao et al 2004;Dagotto 2005;Shenoy et al 2006). While many issues pertaining to these oxides have been understood, their science has many puzzles and challenges in addition to the promise of applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus uneconomical and impractical for large-scale synthesis. The widespread classical cyanation methods to prepare aromatic nitriles are Rosenmund-von Braun 15 and Sandmeyer reactions, 16 in which aryl diazonium and aryl halides are applied as starting materials ( Figure 2). Although these methods are widely exploited, they suffer from some challenges including harsh reaction conditions, metal waste production, and low yields.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, it was observed that the CMR effect was considerably modified when the FMM and antiferromagnetic insulator (AFMI) ground states compete to give a magnetic phase separation state at low temperature. 5 For Mn 3+ -rich compounds, the substitution at the Mn site by a magnetic cation with a formal charge higher than 4+ showed the possibility to create FM in an AFM matrix, because not only it changes the carrier density but also introduces a change of interactions between Mn ions and the substituted cations. 6 Ru is a potential candidate to induce metallicity and ferromagnetism in these manganites due to its ability to adopt two valences Ru 4+ and Ru 5+ , which can both participate to strong super-exchange FM interactions with Mn 3+ .…”
mentioning
confidence: 99%